"Klokka tikker, tiden går": Time and irregular migration. (November 2019) - Brux, Christina; Hilden, Per Kristian; Middelthon, Anne-Lise O
In this paper, which is empirically grounded in ethnographic research conducted among persons living in Norway without legal permission, we explore the temporal dimensions of irregular migration. In the first half, we consider the time aspects of migration control. In particular, we examine the politicization of time within the host of b/ordering policies, practices, and processes through which migrant irregularity is produced and governed in the Norwegian welfare state. We then move into a discussion of migrant irregularity as it is subjectively experienced, in which we solicit time as fundamental unit of analysis with the potential to render phenomenologically intelligible irregularity as it is lived and negotiated. In doing so, we draw upon two classical Greek concepts of time, chronos and kairos, and we consider the conditions of limitation and possibility for reckoning as meaningful experiences of and in time. This entails an exploration of the ways in which the research participants had emplotted their experiences within narratives that they, in retrospect, recalled having crafted at various points in their lives, and of the existential dilemmas that they confronted when these narratives could no longer be sustained. Ultimately, these endeavors produce an analysis of both these meaning-making strategies and what might be understood as the unique temporalities of irregular migration, as it is produced and governed, lived and embodied, and potentially also renegotiated and transformed.